2018
DOI: 10.1007/s12469-018-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of trip chaining behaviour and mode choice using household travel survey data

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In order to render the problem solvable in tractable time, the identification module was constrained to enumerate all tours whose total traveled distance did not exceed 95 km and the number of visited zones (i.e., legs) that did not exceed four. Numerous studies have showcased that the majority of tours do not include more than four legs (Wallner et al, 2018;Schneider et al, 2020). In addition, a brief analysis of the UK National Travel Survey 2016 (Department for Transport, 2017) indicated that only 0.5% of the recorded tours exhibited more than five legs, supporting the argument to limit the maximum number of legs in tours at this level.…”
Section: Parameters For the Identification Modulementioning
confidence: 99%
“…In order to render the problem solvable in tractable time, the identification module was constrained to enumerate all tours whose total traveled distance did not exceed 95 km and the number of visited zones (i.e., legs) that did not exceed four. Numerous studies have showcased that the majority of tours do not include more than four legs (Wallner et al, 2018;Schneider et al, 2020). In addition, a brief analysis of the UK National Travel Survey 2016 (Department for Transport, 2017) indicated that only 0.5% of the recorded tours exhibited more than five legs, supporting the argument to limit the maximum number of legs in tours at this level.…”
Section: Parameters For the Identification Modulementioning
confidence: 99%
“…A few studies on the classification of trips by travel distance can be found in the literature. In the survey of urban residents' travel, the travel distance was subjectively divided into few distance segments, such as 0∼3 km, 3∼6 km, 6∼9 km, 9∼12 km, and longer than 12 km [33,34]. For mode split purpose, only qualitative classification of travel distance (short distance and long distance) was performed [35,36].…”
Section: Trip Length Classification To Test the Hypothesis Of Heterogenous Route Choice Behavior For Trips With Different Lengths The Akamentioning
confidence: 99%
“…On the one hand, visualization techniques collect enormous amount of data (by applying e.g., Geographic Information Systems or sensors on the vehicles) on the movements of citizens then process and analyze the collected information (Wallner et al, 2018). Although an evident merit of this approach is a complete database on the actually conducted trips and number of passengers, the motivation of transport users or non-users remains uncovered.…”
Section: Introductionmentioning
confidence: 99%